1988
DOI: 10.1007/bf01013485
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ecology and the search for marine antifoulants

Abstract: The gorgonian octocoralLeptogorgia virgulata (Phylum Coelenterata, Class Anthozoa) is rarely overgrown by fouling organisms and is avoided by most predators. Laboratory experiments suggest that secondary metabolites and calcium carbonate spicules interact synergistically to provideL. virgulata with an effective defense against predatory fish. In spite of these defenses,L. virgulata is consumed by the symbiotic, trophically specialized gastropodNeosimnia uniplicata, which closely mimics the appearance of the go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 29 publications
0
59
0
Order By: Relevance
“…Gorgonians appear to serve as refuges against predation for palatable algae (Littler et al 1987) and invertebrates (Patton 1972, Gerhart et al 1988). As C. gibbosum feeds, it exposes the axial skeleton of Plexaura homomalla and other gorgonian species (Silveira & Van't Hof 1977, Harvell & Suchanek 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorgonians appear to serve as refuges against predation for palatable algae (Littler et al 1987) and invertebrates (Patton 1972, Gerhart et al 1988). As C. gibbosum feeds, it exposes the axial skeleton of Plexaura homomalla and other gorgonian species (Silveira & Van't Hof 1977, Harvell & Suchanek 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Bakus (1981) demonstrated that most gorgonians and other conspicuous, sessile reef invertebrates contained extractable substances that were toxic to fish. Recent experiments have shown that the calcium carbonate sclerites and secondary metabolites of some gorgonians can deter fish feeding (Gerhart 1984, Pawlik et al 1987, Gerhart et al 1988, Harvell et al 1988, Harvell & Fenical 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulative experiments on the deterrent qualities of spicules in invertebrates or calcified thalli in seaweeds are less extensive and more variable. Spicules from gorgonians (Gerhart et al, 1988;Harvell et al, 1988; and soft corals significantly deter fish feeding, while spicules from an ascidian (Lindquist et al, 1992) and numerous species of sponges do not. Combining these separate assays to determine how chemical and structural defenses might combine to affect prey susceptibilities would be informative, and would more closely mimic the characteristics of real prey.…”
Section: Integrated Pest Managementmentioning
confidence: 99%
“…Several studies have examined the defense capabilities of octocorals, especially gorgonians (Pawlik et al 1987, Harvell & Fenical 1989, Lapid & Chadwick 2006. Both structural (Gerhart et al 1988, Harvell et al 1988) and chemical (Pawlik et al 1987, Harvell et al 1988) attributes of octocorals have demonstrated significant anti-predator defenses against fish and invertebrate predators. For those colonies lying on the seafloor, most of the peduncles and the tissues of the rachis below the polyps (approximately 15 cm) were generally not consumed by Tritonia diomedea.…”
mentioning
confidence: 99%